Occupation exposures and sperm morphology: a case-referent analysis of a multi-centre study. Issue 9 (20th May 2014) - Cherry, Nicola; Povey, Andy C; McNamee, Roseanne; Moore, Harry; Baillie, Helen; Clyma, Julie-Ann; Dippnall, Martin; Pacey, Allan A
Abstract : Objective: We examined occupational exposures and sperm morphology to establish whether exposures implicated differed from those affecting motile sperm concentration. Methods: Computer aided sperm morphometric assessment was undertaken on morphology slides obtained as part of a multi-centre study in 1999–2002 of occupational factors in male infertility. Men attending 14 fertility clinics across the UK were recruited and gave a semen sample. Before results of the semen analysis were known, the men completed detailed questionnaires about their employment and lifestyle. Occupational exposures were assessed by occupational hygienists. Data were analysed using an unmatched case-referent design, allowing for clustering and for confounders. Three case definitions were used: poor morphology (normal morphology <4%), low motile sperm count (MSC) (<4.8×10 6 ) and either condition. Results: Morphology results were available for 1861/2011 men employed at the time of recruitment. Of these 1861, 296 (15.9%) had poor morphology; of the 2011with sperm count, 453 (22.5%) had low MSC; 654/1981 (33.0%) had either condition. Poor morphology, adjusted for confounding, was related to self-reported lifetime exposure to lead (OR=1.33; 95% CI 1.00 to 1.75). Low MSC was also related to self-reported lead and to hygienist-assessed glycol ether exposure. Self-reported use of paint stripper (OR=1.47; 95% CI 1.07 to 2.03) and lead, but not glycol ether, were significantly related to the combined case definition. Conclusions: While this study did not identify any occupational exposure uniquely related to sperm morphology, the capacity of the study to detect risk was increased by including morphology with sperm concentration and motility.